Teachers’ TPACK in Teaching English through Google Classroom Platform - Melinda, Sefi; Sumartono, Sumartono; Rofiudin, Rofiudin (LPPM Universitas Pancasakti Tegal, 2020)
This study concerns with how teachers apply TPACK for teaching English through Google Classroom platform for vocational high school. The objectives of the study are to find out how teachers apply TPACK for teaching English through Google Classroom and the teachers' difficulties in applying TPACK for teaching English through Google classroom platform for vocational high school. The subjects of this research are three English teachers who used Google Classroom platform in teaching English class. An interview was conducted to collect the data and it was described by using the descriptive qualitative method. It showed that learning and teaching process by using Google Classroom is different with face-to-face interaction. It makes teachers must adapt because teacher found difficulty to use any method and strategy when using Google Classroom. Furthermore, teachers prefer to share Pdf or Word files rather than video because video has a large capacity. Students who couldn’t connect their devices to the internet couldn’t fill in the register and were late to submit the assignments.